Patterns of care and outcomes in small cell carcinoma of the prostate: A national cancer database analysis. Issue 12 (11th July 2019) - Metzger, April L.; Abel, Stephen; Wegner, Rodney E.; Fuhrer, Russell; Mao, Shifeng; Miller, Ralph; Beriwal, Sushil; Horne, Zachary D.
Abstract: Background: Small cell carcinoma (SCC) of the prostate is a rare, aggressive disease. Evidence is limited; however, the current standard of care is chemotherapy. The benefit of local treatment modalities is unknown. Methods: We queried the National Cancer Database identifying all SCC/neuroendocrine cases of the prostate, excluding those with unknown nodal or metastatic status, unknown treatment, or those not receiving chemotherapy. Overall survival (OS) was calculated using Kaplan‐Meier curves. Multivariable Cox proportional hazards model was used to identify factors associated with survival. A further subgroup analysis was performed on the utility of local therapy on survival in the nonmetastatic setting. Results: Our final cohort included 657 patients with a median age of 68. Most patients had positive lymph nodes (60.1%) and metastatic disease (70.0%). Median survival was 12 months (95% confidence interval [95% CI], 11.1‐13.3 months) with a median follow‐up of 11.8 months. Metastatic disease, age greater than or equal to 70, omission of androgen deprivation therapy (ADT), and lower income ( P  < .05 for all) were all associated with reduced OS. Patients with prostate‐specific antigen (PSA) greater than or equal to 33 ng/mL and those receiving ADT had better survival ( P  < .05). Those with nonmetastatic disease were more likely to undergo prostatectomy and/or prostatic/pelvic radiation ( P  < .0001). Prostatic/pelvic radiation in the nonmetastatic setting was associated with longer survival ( P  = .02). Though well powered, our study is limited by the selection bias inherent to all observational studies, despite the statistical methods utilized to reduce this effect. Conclusions: Although chemotherapy is the mainstay of treatment, radiation to the prostate/pelvis may be beneficial in the nonmetastatic setting. In addition to chemotherapy, ADT may benefit patients with an elevated PSA.